SMART CITY BASED ON COMMUNITY PARTICIPATION: A SYNERGY OF TECHNOLOGY, GOVERNMENT AND SOCIOLOGY - Basir, Badirun; Abbas, Mohsin (MSJ : Majority Science Journal, 2025)
Smart cities in the past decade have become an important strategy to face urbanization and digital transformation, but their implementation is often technocratic with a focus on infrastructure so that the dimension of community participation receives less attention. This research aims to analyze the role of citizen participation in smart cities, examine the synergy of technology, government, and sociology, and formulate a participatory-based smart city conceptual framework that is inclusive and sustainable, the research was conducted using the Systematic Literature Review (SLR) method on 34 scientific articles published in 2020–2025 which were selected through the process of identification, screening, and thematic synthesis. The results of the analysis show that transparent and responsive digital public services increase citizen trust and encourage participation, although in Indonesia participation still tends to be reactive and depends on local government initiatives. The integration of technology, governance, and social values strengthens transparency, service effectiveness, and policy legitimacy, but its success is determined by the extent to which social and cultural dimensions are accommodated. The conceptual framework offered emphasizes the principles of human-centric and public value, and emphasizes that smart cities should contribute to the achievement of the Sustainable Development Goals (SDGs), this research contributes theoretically by offering an integrative model that combines technology, governance, and social values, as well as practically providing direction for local governments to expand digital literacy, social inclusion, and citizen participation. Follow-up studies are recommended to conduct cross-urban empirical tests to measure the linkage between digital participation, quality of public services, and SDGs achievement.